Achieving Quality of Service through SCalable Aggregate Reservations - Reid, Daniel; Katchabaw, Michael (INFOCOMP Journal of Computer Science, 2006)
Previous attempts at providing widespread Quality of Service (QoS) for the Internet have met with only limited success. Integrated Services and Differentiated Services, the two most popular architectures proposed, suffer from scalability and flexibility concerns respectively. More recently, numerous other architectural proposals have been introduced, but with limited success. This paper introduces a new approach which addresses several issues others have failed to solve effectively. This approach, SCalable Aggregate Reservations (SCAR) is highly scalable, offers additional functionality, and is quite flexible and robust in supporting QoS for networked applications.